Personality Traits and Entrepreneurial Spirit among Fresh Graduates in Klang Valley, Malaysia: - - Mohamed Mohan, Noor Malinda; Tamsir, Fazilah; Ibrahim, Noor Ayuernie; Poniran, Halimi; Muslim, Norjiah`` (Advances in Humanities and Contemporary Studies, 2024)
Entrepreneurship has been viewed as a critical contributor and an economic engine in a country for creating new jobs and it is crucial for graduates to alter their mindset to become self-employed. Thus, it is necessary to synthesize the factors that impact the entrepreneurial intentions of fresh graduates. The aim of this research is twofold; first to identify the extent of entrepreneurial intention and second, to investigate the factors influencing entrepreneurial intention among fresh graduates in Klang Valley, Malaysia. This study utilised an online survey research design with further categorisation and analysis of fresh graduates’ perceptions on their entrepreneurial intention that was gathered via a questionnaire comprising 20 questions based on five assessment criteria. The respondents consisted of 379 fresh graduates from public and private universities. Remarkably, most fresh graduates are having a high level of entrepreneurial intention to start up their business after completing their studies. Further, entrepreneurial behavior, motivation, and risk-taking tendency were proven to have an influence on the intention to entrepreneurship among fresh graduates. Contrary, fresh graduates’ entrepreneurial skills does not influence significantly their entrepreneurial intention. Thus, based on these results, a number of considerations about the most effective role of education in promoting and developing entrepreneurial skills towards entrepreneurship are considered.